Analysis of The Reputation of Youth Resilience Programs In Indonesia; Generation Berencana (Genre) From The Perspective of The Genre Ambassadors - Suharyanti Suharyanti; Qinchara Indra Devinta (Journal Research of Social Science, Economics, and Management, 2022)
The National Family Planning Coordinating Board of Indonesia (BKKBN) launched the Generation Planning (GenRe) as a youth resilience program in response to adolescent issues. The GenRe Ambassadors (GA) are role models whose job is to socialize and persuade young people in Indonesia to behave in a healthy manner. GenRe E Indonesia is an organization that accommodates GenRe Ambassadors. The success of Gnere Ambassadors in carrying out their duties is also determined by how they perceive the reputation of the organization they shelter. The purpose of this research is to know the reputation of GenRe Indonesia as perceived by Duta GenRe by using the dimension of reputation. This research approach is qualitative and employs phenomenological methods. The informants are the GenRe Ambassadors , who have served as ambassadors for 2–3 years. Sampling was carried out using a snowball technique for further in-depth interviews. The result of this study is emotional appeal, which is the strongest dimension in shaping positive perceptions of GenRe Indonesia. Meanwhile, in the dimensions of workplace and development, financial and coordination constraints are factors that form unsatisfactory perceptions for GenRe Ambassadors. Considering the emotional connection that is formed, it should be the concern of BKKBN and GenRe Indonesia to immediately respond to the GenRe Ambassador's dissatisfaction.